Paris Terrorism Attacks: Interdisciplinary Studies of Insider Trading and Money Laundering on Global Scale - Stefano de Nichilo; Rahma Sandhi Prahara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
In this paper, we investigate past research and the development of knowledge and practice in the area of countering money laundering and terrorist financing. Additionally, we draw attention to the gaps in the preventive mechanisms adopted by countries to fight against AML & ATF and to highlight areas for possible future research. There are various avenues to invest and one of those is Stock Market. But the decision of the investor depends on various factors. One of the factors which affects the behavior of investment is Terrorism. The paper focuses on short run and long run association and influence of terrorism on major global stock indices and Gold. We have taken Paris attacks of 2015 as base and ARDL model is used to study the short run and long run impact on the selected stock indices. We find that terrorism has got short run impact on the global indices but there is no long run impact.